Thermosensitive polymer controlled morphogenesis and phase discrimination of calcium carbonate. Issue 48 (1st June 2017) - Jiang, Jun; Tauer, Klaus; Qiu, Yun-Hao; Zhong, Ya-Xu; Gao, Min-Rui; Antonietti, Markus; Yu, Shu-Hong
Abstract : Homogeneous aragonite flowers with controlled surface structures can be synthesized by using a thermosensitive polymer, i.e. poly(ethylene glycol)–poly( N -isopropyl acrylamide)–poly(acrylamido methyl propane sulfonate) (PEG–PNIPAM–PAMPS), as a crystal growth modifier in the mineralization of calcium carbonate. Abstract : Homogeneous aragonite flowers with controlled surface structures can be synthesized by using a thermosensitive polymer, i.e. poly (ethylene glycol)–poly( N -isopropyl acrylamide)–poly(acrylamido methyl propane sulfonate) (PEG–PNIPAM–PAMPS), as a crystal growth modifier in the mineralization of calcium carbonate.